DINOFLAGELLATE CYST STRATIGRAPHY OF THE SCISTI A FUCOIDI FORMATION (EARLY CRETACEOUS) FROM PIOBBICO, CENTRAL ITALY: CALIBRATED EVENTS FOR THE ALBIAN OF THE TETHYAN REALM (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
Rich and well preserved organic-walled dinoflagellate cyst assemblages recovered from the Scisti a Fucoidi Formation at Piobbico, central Italy are presented. Distributions of 83 taxa, plotted against the independent stratigraphic framework established from planktonic foraminifers and nannofossils, are compared with ranges documented in the literature in order to identify and calibrate reference horizons for the Albian dinoflagellate cyst stratigraphy of the Tethyan Realm. The following events have been selected: the lowest occurrences of Kleithriasphaeridium atlasiense and Tehamadinium coummia at the Aptian/Albian boundary, of Leberidocysta defloccata in the Lower Albian, of Adnatosphaeridium tutulosum, Litosphaeridium arundum and Ovoidinium sp. A sensu Davey (1979) in the Middle Albian, of Dapsilidinium? pumilum, Litosphaeridium conispinum, Tehamadinium mazaganense and Hapsocysta dictyota in the Upper Albian; the highest consistent occurrences of Hapsocysta peridictya in the Lower Albian, of Codoniella psygma and Damassadinium chibane in the Middle Albian, of Tehamadinium sousense in the Upper Albian.
Keywords: Biostratigraphy; dinoflagellate cysts; Early Cretaceous; Albian; Tethyan Realm; central Italy